Android-based interactive ethnoscience E-LKPD containing science technology society models to improve critical thinking skills - Abshor, Devy Aufia; Wibowo, Deki; Zukhruf, Afriza Meigi; Sholihah, Afifah Mar’atus; Rahma, Dian Aulia (Indonesian Journal of Educational Development (IJED), 2025)
This research aims to develop an Android-based interactive E-LKPD with ethnoscience content and a Community Science and Technology model to improve students' critical thinking skills. The urgency is to provide innovative solutions for social studies learning by integrating Android-based science, technology, and local culture to increase interactivity and critical thinking in daily life. The method is Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The population is 1 classroom teacher, 18 students, and 4 experts. The sampling technique uses purposive sampling. Data collection techniques, observation, interviews, tests, response questionnaires, and documentation. There are three data analyses: needs analysis, validity analysis, and practicality analysis. Needs analysis, teachers, and students need developed products. The validity of the E-LKPD is rated very valid (89.23%), while its practicality is rated very practical (90.83%). It was concluded that this E-LKPD is feasible and useful for improving students' critical thinking skills. Based on the research results, it is recommended that teachers take advantage of the Android-based ethnoscience E-LKPD and that schools support the application of learning technology.